Transamerica Belladonna Productions presents ; written and directed by Duncan Tucker ; produced by Linda Moran, René Bastian, Sebastian Dungan.. - Huffman, Felicity 1962-; Zegers, Kevin 1984-; Flanagan, Fionnula 1941-; Young, Burt 1940-; Preston, Carrie 1967-; Evans, Venida 1047-; Budinoff, Jon; Scheine, Raynor 1942-; Peña, Elizabeth 1961-; Greene, Graham 1952- (2007)
A pre-operative transsexual learns that she fathered a child years earlier.